Efektivitas Penggunaan Media Pembelajaran Terhadap Terminologi Medis di STIKES Sapta Bakti - Liza Putri; Novi Lasmadasari; Khairunnisa (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Objective singer to review determine the effect of instructional media using animation video ( the animaker) against hearts caring for medical recort student at Sapta Bakti Stikes. The singer is a quantitative research study with quasi experimental method. The study design used hearts singer that pre-post test design with a control group, because researchers want to compare the dependent variable between 2 groups. Study design the singer used to review test the effect of instructional media using the animaker against hearts medical recort student at Sapta Bakti Stikes. Knowledge measurement was carried out before being given treatment (pre-test) and after being given treatment (post-test). The average pre-test score in the control group was 59.17 while in the intervention group it was 62.00 with a p value of 0.375. So it can be concluded that there is no difference in the average knowledge value of the two groups (p>0.05). In 2 groups there was an increase in the post-test, in the intervention group, the score was 78.05 with a standard deviation of 11.40. While in the control group the score is 70.11 with a standard deviation of 10.43. The results of the statistical test analysis showed that the pre-post test value was p = 0.005, meaning that there was a significant difference between the average knowledge value of the intervention group and the control group (p <0.05). so there was an increase in the intervention group that used video as well as the observation of the respondent's activity experiencing a significant change.